The predictive power of macroeconomic variables on stock market returns: the case of the Athens Stock Exchange - Νιάρχος, Νικήτας Α.; Αλεξάκης, Χρήστος Α. (SPOUDAI Journal of Economics and Business, 2000)
The purpose of this study is to investigate whether it is possible to predict stock market returns with the use of macroeconomic variables in the Athens Stock Exchange. The emerging stock market of Greece, is a small and relatively underinvestigated market. Hence, there is a possibility that a predictive model may exist for stock returns, violating the Efficient Market Hypothesis (E.M.H.) which states that stock market returns cannot be predicted. In the international literature there is a wide variety of methods used for predictive purposes. In this study we have used cointegration analysis, and as explanatory variables some macroeconomic factors which are believed by economists and market practitioners, to influence stock returns. Namely the macroeconomic predictive variables are, the inflation rate measured by the Consumer Price Index, the M3 measure of money supply and the exchange rate of US Dollar/Greek Drachmae. JEL Classification: G14